2013
DOI: 10.1038/bjc.2013.116
|View full text |Cite
|
Sign up to set email alerts
|

Cohort study of adherence to adjuvant endocrine therapy, breast cancer recurrence and mortality

Abstract: Background:Adjuvant endocrine therapy is recommended for women with oestrogen receptor-positive breast cancer, but many women do not take the medication as directed and they stop treatment before completing the standard 5-year duration.Methods:This retrospective cohort study conducted between 1993 and 2008 of all women with incident breast cancer, who are residing in the Tayside region of Scotland, examined adherence to prescribed adjuvant tamoxifen or aromatase inhibitors (AIs). Survival analysis examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
200
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(223 citation statements)
references
References 24 publications
(44 reference statements)
14
200
2
1
Order By: Relevance
“…This relation has also been observed in previous studies 6,23 , in which women with more involved lymph nodes presented a higher rate of discontinuity and, as a consequence, lower success in the employed therapy, which also reaffirms the known inverse relation between the survival rate and the cancer stage at the moment of diagnosis 7 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This relation has also been observed in previous studies 6,23 , in which women with more involved lymph nodes presented a higher rate of discontinuity and, as a consequence, lower success in the employed therapy, which also reaffirms the known inverse relation between the survival rate and the cancer stage at the moment of diagnosis 7 .…”
Section: Discussionsupporting
confidence: 85%
“…Nevertheless, the desirable results many times are not achieved due to problems such as low adherence and low persistence in the recommended treatment, whose associated factors should be carefully evaluated. Evidence ensures that benefits in the change from the mortality and disease recurrence rates only happen effectively if the treatment is completely followed 6,7 . Attention has been given to adherence and persistence studies (A & P) due to the concept that clinical results of the treatment are not only affected by how patients take the drugs, but also by the period of uninterrupted use 8 .…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Studies have consistently demonstrated lower compliance in real-world practice than in clinical trials. [28][29][30] Although a clinical trial demonstrated similar efficacy and differing safety profiles of pazopanib and sunitinib as …”
Section: ■■ Discussionmentioning
confidence: 99%
“…For the 1-year time point, average rates of adherence to endocrine therapy ranged from 77% [33] to 100% [34], with 23% [35,36] to 40% [29] of patients meeting criteria for poor adherence according to a particular threshold (i.e., medication possession ratio ,80%). Longitudinal investigations show that rates of adherence to oral endocrine therapy generally decline over time, with some studies showing rates dropping to approximately 50% adherence by 5-year follow-up [14,33,35,37]. Also shown in Table 3, a total of 19 studies addressed rates of adherence to oral nonendocrine antineoplastic therapies in samples of patients with various cancer types: 47.4% (n 5 9) chronic myeloid leukemia, 26.3% (n 5 5) mixed cancers, 15.8% (n 5 3) breast cancer, 5.3% (n 5 1) hepatocellular carcinoma, and 5.3% (n 5 1) gastrointestinal cancer.…”
Section: Rates Of Adherence To Oral Antineoplastic Therapiesmentioning
confidence: 99%
“…Published reviews reveal quite variable, and sometimes alarmingly low, rates of adherence to these medications, even as low as 16% [9][10][11][12]. Moreover, studies show statistically significant associations between medication nonadherence and clinical and utilization outcomes, including cancer progression, more inpatient days, higher total health care spending, and worse survival [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%